A National Public Health Workforce to Control COVID-19 and Address Health Disparities in the United States. (1st July 2021) - Kilmarx, Peter H; Long, Theodore; Reid, Michael J A
Abstract: A large, well-trained public health workforce is needed to control coronavirus disease 2019 (COVID-19) in the United States in the short term and to address other disease burdens and health disparities in the long run. As the public health workforce declined following the 2008 financial crisis, many US jurisdictions struggled to hire a sufficient number of staff for roles initially including testing and contact tracing and more recently for vaccination. Ultimately, COVID-19 control will require a combination of vaccination and rapid investigation, contact tracing, and quarantine to stop chains of transmission. New federal resources for a public health workforce have been made available. With appropriate attention to addressing administrative barriers and ensuring equity, a 21st-century US public health workforce will hasten the control of COVID-19, provide economic relief to individuals and communities, and reduce the burden of other infectious diseases, noncommunicable diseases, and other disease burdens. A long-term commitment to a robust public health workforce is vital to ensuring health security and preparedness for future health threats.